Promoting Fishpreneurship to Develop Entrepreneurial Interest for the Students of Politeknik Muhammadiyah Magelang Dealing with Covid-19 Pandemic - Kusuma Anggraini, Rr. Citra Permata; Subarkah, Rachmat (Agrikan Jurnal Agribisnis Perikanan, 2022)
The Covid-19 Pandemic has had a big impact on the employment sector, especially layoffs for workers. One of the means that can be done to survive during this pandemic is entrepreneurship. Universities have a role to prepare graduates who are capable of entrepreneurship. Fishpreneurship, a development of a fishery-based entrepreneurship learning method, aims to foster entrepreneurial interest for the students of Politeknik Muhammadiyah Magelang. The method used in this study is the Participatory Learning Action System (PLAS) with several stages of awareness phase, mentoring phase, and institutionalization phase. This study was done in May until September 2021 in Politeknik Muhammadiyah Magelang. The media of learning entrepreneurship applied in this study was a fish farming in buckets starting from sowing seeds, maintenance, to harvesting and marketing. The catfish type used in this study was a pearl catfish of Clarias gariepinus. The catfish farming in buckets, which was done for 69 days, obtained an absolute weight of 66.88 gram, SGR 96.92%, FCR 0.86, SR 93.33%, and the absolute length of 9.73 cm. In the phase of institutionalization, it was done by inaugurating students to become members of the Student Activity Units or known as Unit Kegiatan Mahasiswa (UKM) of Polimmag Preneur which was established to provide a place for the students to do some activities of fishery-based entrepreneurship. From this study, it can be concluded that fishpreneurship is able to develop the entrepreneurial interest for the students of Politeknik Muhammadiyah Magelang.